Mobile Applications Design in Fatigue Risk Management - PERSSON, ANTON; ANDERSSON, JOHANNES (My University, 2013)
This report describes the redesign and development of the iPhone application CrewAlert. The application is intended for use by pilots as a tool for assessment, logging and reporting of fatigue, to increase safety in the air. It also keeps track of the user's schedule, and sleep pattern. The application is developed from being only a iPhone application to being a fully universal iOS application supporting all iOS devices and screen orientations. Focus of development lies on usability and feature set, using the Goal Directed Design approach in combination with the Scrum framework. As development progressed the focus was put towards lowering the learning curve and creating more substance for the users in every day use.
Keywords: Interaktionsteknik; Interaction Technologies